Pengembangan Modul PAI Berbasis Nilai-Nilai Keseimbangan Dalam Pemahaman Islam Wasathiyah Di SMA Negeri Ploso - Winda Ayu Safitroh; Machnunah Ani Zulfah (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
The Islamic wasathiyah value of tawazun embodies the principles of moderation and equilibrium in Islam. Tawazun Islam Wasathiyah underscores the significance of observing limits in all aspects of life, avoiding extremism and excess. In social and political spheres, the Islamic wasathiyah value of tawazun promotes wisdom, tolerance, and peaceful conflict resolution through dialogue and diplomacy Educationally, this approach fosters a profound comprehension of moderate values, interfaith dialogue, and appreciation for cultural diversity. Consequently,a field study was conducted to investigate the efficacy of PAI module teaching materials in cultivating students' understanding of Islamic Wasathiyah, including the values of balance, among ninth-grade students at Ploso State High School. This research aims to contribute to fostering an attitude of balance and tolerance among different religions.